ANALISIS SISTEM KEAMANAN DATA UNIVERSITAS BINA INSAN DARI KEJAHATAN SIBER MENGGUNAKAN PENDEKATAN METODE OWASP - Susanto, Erwin; Herdiansyah, M. Izman; Negara, Edi Surya; Damayanti, Nita Rosa (Jurnal Teknologi Informasi Mura, 2026)
This study aims to analyze the data security system at Universitas Bina Insan against cybercrime threats using the Open Web Application Security Project (OWASP) Top 10 approach. Data security is an important aspect because higher education institutions store sensitive information such as academic data, user identities, and administrative records. This research uses a qualitative method with data collection techniques through interviews, observations, documentation studies, as well as web application security testing using OWASP ZAP. The results show that the system has implemented basic security measures; however, several vulnerabilities that may pose risks were still found, such as injection, cross-site scripting (XSS), weaknesses in authentication and access control, and suboptimal security configurations with risk levels ranging from low to high. Questionnaire findings support the technical results and indicate that OWASP Top 10 is effective as a framework for identifying, evaluating, and mitigating vulnerabilities. This study provides comprehensive prevention strategy recommendations to improve data security continuously.